Sex-Differences in Renal Expression of Selected Transporters and Transcription Factors in Lean and Obese Zucker Spontaneously Hypertensive Fatty Rats - Andrea Babelova; Birgitta C. Burckhardt; Waja Wegner; Gerhard Burckhardt; Maja Henjakovic (Journal of Diabetes Research)
The aim of this study was to identify sex-dependent expression of renal transporter mRNA in lean and obese Zucker spontaneously hypertensive fatty (ZSF1) rats and to investigate the interaction of the most altered transporter, organic anion transporter 2 (Oat2), with diabetes-relevant metabolites and drugs. Higher incidence of glomerulosclerosis, tubulointerstitial fibrosis, and protein casts in Bowman’s space and tubular lumen was detected by PAS staining in obese male compared to female ZSF1 rats. Real-time PCR on RNA isolated from kidney cortex revealed that Sglt1-2, Oat1-3, and Oct1 were higher expressed in kidneys of lean females. Oct2 and Mrp2 were higher expressed in obese males. Renal mRNA levels of transporters were reduced with diabetic nephropathy in females and the expression of transcription factors Hnf1β and Hnf4α in both sexes. The highest difference between lean and obese ZSF1 rats was found for Oat2. Therefore, we have tested the interaction of human OAT2 with various substances using tritium-labeled cGMP. Human OAT2 showed no interaction with diabetes-related metabolites, diabetic drugs, and ACE-inhibitors. However, OAT2-dependent uptake of cGMP was inhibited by furosemide. The strongly decreased expression of Oat2 and other transporters in female diabetic ZSF1 rats could possibly impair renal drug excretion, for example, of furosemide.